2013
DOI: 10.1002/jor.22412
|View full text |Cite
|
Sign up to set email alerts
|

Tendon gradient mineralization for tendon to bone interface integration

Abstract: Tendon-to-bone integration is a great challenge for tendon or ligament reconstruction regardless of use of autograft or allograft tendons. We mineralized the tendon, thus transforming the tendon-to-bone into a “bone-to-bone” interface for healing. Sixty dog flexor digitorum profundus (FDP) tendons were divided randomly into 5 groups: 1) normal FDP tendon, 2) CaP (Non-extraction and mineralization without fetuin), 3) CaPEXT (Extraction by Na2HPO4 and mineralization without fetuin), 4) CaPFetuin (Non-extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Emerging efforts have begun to shift focus from homogenous biomaterials for the purpose of regenerating a single tissue (Caliari et al, 2011; Ferreira et al, 2012; Galatz et al, 2006; Kanungo et al, 2008; Levingstone et al, 2014; Mathew et al, 2012) to multi-compartment and spatially graded biomaterials for the express purpose of repairing more complex tissues such as the tendon-to-bone junction (Caliari et al, 2015a; Harley et al, 2010; Lipner et al, 2014; Qu et al, 2013; Smith et al, 2016; Weisgerber et al, 2015; Weisgerber et al, 2013b). Efforts in our lab have recently described two new variants of collagen scaffolds under development for osteotendinous repair applications.…”
Section: : Introductionmentioning
confidence: 99%
“…Emerging efforts have begun to shift focus from homogenous biomaterials for the purpose of regenerating a single tissue (Caliari et al, 2011; Ferreira et al, 2012; Galatz et al, 2006; Kanungo et al, 2008; Levingstone et al, 2014; Mathew et al, 2012) to multi-compartment and spatially graded biomaterials for the express purpose of repairing more complex tissues such as the tendon-to-bone junction (Caliari et al, 2015a; Harley et al, 2010; Lipner et al, 2014; Qu et al, 2013; Smith et al, 2016; Weisgerber et al, 2015; Weisgerber et al, 2013b). Efforts in our lab have recently described two new variants of collagen scaffolds under development for osteotendinous repair applications.…”
Section: : Introductionmentioning
confidence: 99%
“…Although there is evidence that PAsp may act as an inhibitor when not bound to collagen [60]. Prior studies examining the mineralization of dense collagen scaffolds with fetuin have demonstrated similar results: mineralization occurs preferentially within the matrix, often concentrated near the surface, likely due to diffusion limitations [20,53,61]. Unlike SBF mineralization, which resulted in a two-layer composite, the addition of fetuin led to the formation of micrometre-scale inclusions leading to a particle inclusion composite.…”
Section: Discussionmentioning
confidence: 85%
“…Lines above bars indicate p , 0.05. rsfs.royalsocietypublishing.org Interface Focus 6: 20150070 techniques have been employed. These included simply immersing collagen scaffolds in solutions such as SBF or adding proteins, peptides or other chemicals to help control the mineralization process [3,20,[51][52][53][54][55][56][57]. Simple immersion of collagen leads to surface deposition of mineral either on the surface of fibrils, creating extrafibrillar mineral, or on the surface of dense collagen scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…The indentation test was performed in accordance with the previously established method(Qu et al, 2013). Samples were cut into segments (the same site as for the friction test) to a length of 2 cm.…”
Section: Methodsmentioning
confidence: 99%